Genetic diversity analysis of Puan Kalianda kopyor coconuts (Cocos nucifera) from South Lampung, Indonesia based on SSR markers (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Rahayu MS, Setiawan A, Maskromo I, Purwito A, Sudarsono. 2021. Genetic diversity analysis of Puan Kalianda kopyor coconuts (Cocos nucifera) from South Lampung, Indonesia based on SSR markers. Biodiversitas 23: 205-211. Puan Kalianda kopyor coconut (Cocos nucifera L.) is a newly released tall kopyor coconut from Kalianda, South Lampung, Indonesia. The kopyor coconut is an exotic, highly economic value coconut mutant with an abnormal endosperm. This study aimed to analyze the genetic diversity of Puan Kalianda kopyor coconut from South Lampung, Indonesia using SSR markers. As many as 91 Puan Kalianda kopyor coconut accessions were genotyped using 10 SSR marker loci, and the generated data were used to evaluate their genetic diversity and population structure. The results showed a high degree of SSR marker polymorphism (PIC value = 67%), indicating the SSR marker loci are informative for revealing the genetic diversity within the evaluated Puan Kalianda kopyor coconut population. The Puan Kalianda coconut population showed a 70% expected heterozygosity (He) and 60% observed heterozygosity. The phylogenetic analysis formed two main clusters, and each cluster consisted of three sub-clusters. The Genetic structure analysis showed that the population most probably derived from two ancestral origins (K = 2) and can further be clustered into six sub-clusters (K = 6). Therefore, since genetic diversity within the population is relatively high, the Puan Kalianda tall kopyor coconut population can be considered an essential genetic resource for future kopyor coconut development.
Keywords: Coconut mutant; Tall coconuts; Genetic diversity analysis; Simple sequence repeats; Abnormal endosperm